Makrokonstruktionen Komplexe Adverbialstrukturen zwischen lokaler Emergenz und Sedimentierung im gesprochenen Französisch - Ehmer, Oliver (Linguistik - Impulse & Tendenzen, 2022)
The study investigates adverbial structures in spoken French that combine three or more discursive elements in a complex way. These structures are modeled in accordance with the terms of construction grammar as "macro constructions." Drawing upon an extensive corpus, this study analyzes them with regard to their local emergence in interaction and their sedimentation.